2023
DOI: 10.1021/acs.jmedchem.2c01191
|View full text |Cite
|
Sign up to set email alerts
|

BET–HDAC Dual Inhibitors for Combinational Treatment of Breast Cancer and Concurrent Candidiasis

Abstract: Breast cancer is susceptible to Candida infections, and candidiasis has an enhancing effect on the progression and metastasis of tumor. Breast cancer and concurrent candidiasis represent a significant challenge in clinical therapy. Herein, a series of novel small molecule inhibitors simultaneously targeting bromodomain and extra-terminal (BET) and histone deacetylase (HDAC) were designed for combinational treatment of breast cancer and resistant Candida albicans infections. Among them, compounds 13c and 17b ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Given the synergistic effect of simultaneously blocking BET and HDAC in cancer cell processes, our group and others have identified several classes of BET–HDAC dual inhibitors for the treatment of cancer. In particular, we found that BRD4–HDAC dual inhibitors showed potent activity for the combinational treatment of cancer and concurrent candidiasis . Inspired by these therapeutic advantages, herein, a series of new BRD4–HDAC dual inhibitors were designed and evaluated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given the synergistic effect of simultaneously blocking BET and HDAC in cancer cell processes, our group and others have identified several classes of BET–HDAC dual inhibitors for the treatment of cancer. In particular, we found that BRD4–HDAC dual inhibitors showed potent activity for the combinational treatment of cancer and concurrent candidiasis . Inspired by these therapeutic advantages, herein, a series of new BRD4–HDAC dual inhibitors were designed and evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…37−41 In particular, we found that BRD4−HDAC dual inhibitors showed potent activity for the combinational treatment of cancer and concurrent candidiasis. 42 Inspired by these therapeutic advantages, herein, a series of new BRD4−HDAC dual inhibitors were designed and evaluated. Interestingly, these dual inhibitors showed improved selectivity toward fungal HDACs, leading to a strong synergistic effect in combination with FLC for treating resistant C. albicans infections.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Epigenetic modifications are able to modulate gene expression changes, including in pain circuits. There is growing evidence that histone acetylation plays a key role in the development and maintenance of chronic pain. Serving as epigenetic “readers” of acetylated lysines on histone tails, the bromodomain and extra-terminal (BET) domain family proteins could regulate the expression of genes involved in chronic pain by enriching the corresponding transcription factors at the promoter regions of these genes. Recently, BET bromodomain (BET BD) inhibition has also been revealed to alleviate nerve injury-induced NP by ameliorating nerve inflammation and modulating the expression of critical ion channels to reduce neuronal excitability. The BET protein family is composed of bromodomain-containing protein 4 (BRD4), BRD3, BRD2, and testes-specific BRDT, each of which contains two tandem BDs, BD1 and BD2, and an extra-terminal domain. BD1 and BD2 are essential domains for the BET proteins to perform their functions. Each BD consists of approximately 110 amino acids and forms four reverse parallel α-helices (αZ, αA, αB, and αC) and two hydrophobic loops (ZA loop and BC loop). The end of the α-helices and the surfaces of the hydrophobic loops together form the acetylated lysine binding pocket, containing a conserved asparagine that forms a hydrogen bond interaction with the acetylated lysine, a hydrophobic residue called the gatekeeper that controls the entry of the acetylated lysine, a hydrophobic WPF shelf adjacent to the ZA loop, and a ZA channel. …”
Section: Introductionmentioning
confidence: 99%
“…Several small-molecule BET inhibitors were developed for early clinical development or in preclinical studies. High efficacy and positive results were found for BET inhibitor treatment of hematological malignancies, such as ovarian cancer, metastatic prostate cancer, breast cancer, and small-cell lung cancer . However, some probes designed as early tools exhibited weak and poorly selective binding; thus, it was necessary to develop novel well-characterized probes to ascertain the function of bromodomain family members. In addition, some pan-BD inhibitors (defined as having similar inhibitory activity for BD1 and BD2 of BET proteins including the eight bromodomains) have potential applications for academic research or drug development, such as JQ1, I-BET151, ZEN-3694, OTX-015, , NHWD-870, and ABBV-075 (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Several small-molecule BET inhibitors were developed for early clinical development or in preclinical studies. 24−30 High efficacy and positive results were found for BET inhibitor treatment of hematological malignancies, 31−34 such as ovarian cancer, 35 metastatic prostate cancer, 36 breast cancer, 37 and small-cell lung cancer. 38 However, some probes designed as early tools exhibited weak and poorly selective binding; thus, it was necessary to develop novel well-characterized probes to ascertain the function of bromodomain family members.…”
Section: Introductionmentioning
confidence: 99%